Preparation method of implanted spongy agent low in side effect incidence rate, high in safety and capable of rapidly relieving pain for long time

Through the combination of sodium hyaluronate and ropivacaine and auxiliary materials, a sustained-release implanted sponge agent was prepared, which solved the problems of short pain relief time and high side effects in the prior art, and achieved rapid, long-term and safe Pain relief effect.

CN119185651APending Publication Date: 2024-12-27DONGFANG YANMEI (CHENGDU) BIOTECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411333806.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-24
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

The local anaesthetics commonly used in existing medical beauty fillers have short-acting and high side effects, which cannot meet the clinical needs of implanted sponge agents for long-term pain relief.

Method used

Use salts or complexes formed by sodium hyaluronate and ropivacaine as the main sustained release material, combining hydroxypropyl cellulose, crosslinked sodium hyaluronate and calcium salts, and partial carboxylic sodium of sodium acid hyaluronate Acidification and calcium ion substitution to form a colloidal solution to sustained release of ropivacaine, and combined with collagen and glutamyl endopeptidase, a membrane-like or spongy implanted sponge agent is prepared.

Benefits of technology

It achieves a rapid and long-term pain relief effect, reduces the incidence of adverse reactions, has good stability, is salt tolerance and high ionic strength, and avoids the problem of rapid release of drugs at one time.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005057724180000141
    Figure BDA0005057724180000141
  • Figure BDA0005057724180000151
    Figure BDA0005057724180000151
  • Figure BDA0005057724180000152
    Figure BDA0005057724180000152
Patent Text Reader

Abstract

The invention discloses a preparation method of an implanted sponge agent, which comprises the following steps: dispersing sodium hyaluronate with small molecular weight, sodium hyaluronate with medium and small molecular weight and hydroxy propyl cellulose with medium viscosity in water, and adding a hydrochloric acid solution to convert the sodium hyaluronate into acidic sodium hyaluronate; adding prototype ropivacaine nanoscale powder or a dispersion liquid of water of the prototype ropivacaine nanoscale powder; ropivacaine hydrochloride is added; cross-linked sodium hyaluronate is added; adding a calcium salt solution; adding an aqueous solution of collagen and an aqueous solution of glutamyl endopeptidase, so that the collagen is basically crosslinked; and filling the solution into a container, freeze-drying, and removing the solvent. The implant sponge agent has the advantages of low side effect occurrence rate, high safety, rapidness, long-term pain relieving and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] A method for preparing an implantable sponge, specifically a method for preparing an implantable sponge with low side effect incidence, high safety and long-term analgesia. Technical Background

[0002] Injectable cosmetic procedures involve injecting specific fillers to enhance facial contours and fill in hollows and fine lines. This technique uses a fine needle to deliver specific ingredients into specific areas to enhance contours, add volume, and improve wrinkles. Injectable cosmetic procedures can achieve more natural results, and fillers can be customized to suit individual facial features and needs.

[0003] In order to relieve pain after injection, lidocaine local anesthetic is generally added to existing medical cosmetic fillers.

[0004] However, lidocaine's duration of action for local infiltration anesthesia is relatively short, typically 0.5 to 2 hours. Furthermore, it can cause symptoms such as nausea, dizziness, palpitations, and sweating, has a high adverse reaction rate, and offers limited, non-progressive motor blockade, resulting in less pronounced sensorimotor dissociation and high cardiac and central nervous system toxicity.

[0005] Among the above-mentioned medical cosmetic fillers, the local infiltration anesthesia of lidocaine is slightly prolonged and can last for several hours. However, the pain of the patient after injection may last for several days, especially for implanted sponges, which cannot meet clinical needs.

[0006] Therefore, in the above-mentioned medical cosmetic fillers, especially implantable sponges, it is necessary to add local anesthetics with lower side effect rates, higher safety and longer anesthesia time.

[0007] Ropivacaine has numerous advantages over lidocaine. It has a lower incidence of adverse reactions such as nausea, dizziness, palpitations, and sweating. It provides a strong, localized, non-progressive motor blockade, enhancing sensorimotor dissociation, and exhibits lower cardiac and central nervous system toxicity. Local infiltration anesthesia has a relatively long duration of action, generally 2 to 6 hours, but this still does not meet clinical treatment needs.

[0008] Therefore, in reality, it is necessary to prepare a ropivacaine implant sponge with lower side effect rate, higher safety, faster speed and longer analgesia time, and the analgesia time should be consistent with clinical needs, neither too long nor too short. Summary of the Invention

[0010] The present invention relates to a method for preparing an implant sponge with low side effect incidence, high safety, rapid effect and long-term analgesia, the method comprising:

[0011] 1) Sodium hyaluronate with a molecular weight of 2000 to 10,000 Daltons, sodium hyaluronate with a molecular weight of 50,000 to 100,000 Daltons, and medium-viscosity hydroxypropyl cellulose with a molecular weight of 100,000 to 200,000 Daltons (e.g., Klucel JF (having a molecular weight of approximately 140,000 Daltons and a viscosity of 150-400 mPa·s at a concentration of 5% wt / wt)) are dispersed in water, wherein the concentration of the sodium hyaluronate with a molecular weight of 2000 to 10,000 Daltons is 20-30% wt / wt (based on the final total amount of 100%, i.e., 20-30 parts per 100 parts by weight), and the concentration of the sodium hyaluronate with a molecular weight of 50,000 to 100,000 Daltons is 10-15% wt / w. t (based on the final total amount of 100%, i.e., 10-15 parts per 100 parts by weight), the concentration of hydroxypropyl cellulose is 2-6% wt / wt (based on the final total amount of 100%, i.e., 2-6 parts per 100 parts by weight), hydrochloric acid solution is added to convert sodium hyaluronate into acid sodium hyaluronate, wherein the molar amount of hydrochloric acid is 0.7-0.8 times the molar amount of total sodium in the sodium hyaluronate, and the mixture is mixed to obtain colloidal solution A;

[0012] 2) Adding prototype ropivacaine nanometer powder or its aqueous dispersion to colloidal solution A, wherein the molar amount of ropivacaine is 0.95-1 times of the molar amount of the hydrochloric acid in the above-mentioned hydrochloric acid solution; and adding ropivacaine hydrochloride, wherein the molar amount of ropivacaine is 0.4-0.8 times of the molar amount of the hydrochloric acid in the above-mentioned hydrochloric acid solution, mixing, and leaving at room temperature for 8-24 hours to obtain colloidal solution B;

[0013] 3) Adding cross-linked sodium hyaluronate with a molecular weight of 800,000-1.2 million Daltons to colloidal solution B at a concentration of 1-5% wt / wt (based on the final total amount of 100%, i.e., 1-5 parts per 100 parts by weight) to obtain colloidal solution C;

[0014] 4) Adding a calcium salt solution to colloidal solution C and mixing until 10% to 20% of the total molar amount of sodium ions in the three sodium hyaluronates is replaced by calcium ions, mixing, and allowing to stand at room temperature for 1-3 days to form colloidal solution D;

[0015] 5) adding an aqueous solution of collagen and an aqueous solution of glutamyl endopeptidase to the colloidal solution D, respectively, wherein the concentration of the collagen is 1-8% wt / wt (based on the final total amount of 100%, i.e., 1-8 parts per 100 parts by weight), the ratio of the amount of the glutamyl endopeptidase to the collagen is 1-15 U / g, and after mixing, the temperature is maintained at 0°C to 4°C for 24-72 hours to allow the collagen to be substantially cross-linked, thereby obtaining a colloidal solution E;

[0016] 6) The colloidal solution E is placed in a container so that the liquid layer thickness is 1-2 mm, and then freeze-dried to remove the solvent. DETAILED DESCRIPTION

[0017] The concentration of the sodium hyaluronate with a molecular weight of 2000 to 10,000 (Daltons) is preferably 23-28% wt / wt.

[0018] The concentration of the sodium hyaluronate with a molecular weight of 50,000 to 100,000 (Daltons) is preferably 12-13% wt / wt.

[0019] The concentration of the hydroxypropyl cellulose is preferably 3-4% wt / wt.

[0020] The above calcium salts include but are not limited to calcium chloride, calcium acetate, calcium nitrate, calcium hydroxide or mixtures thereof.

[0021] The usage ratio of the sodium hyaluronate with a molecular weight of 2000 to 10,000 (Daltons) to the sodium hyaluronate with a molecular weight of 50,000 to 100,000 (Daltons) is 2:0.8-1, preferably 2:0.9-1.

[0022] The concentration of the collagen is preferably 3-6% wt / wt.

[0023] The ratio of the amount of the glutamyl endopeptidase to the amount of the collagen is preferably 3-10 U / g, more preferably 4-7 U / g.

[0024] The thickness of the liquid layer is preferably 1.3-1.8 mm.

[0025] The preparation method of the implant sponge of the present invention also includes further preparing the sponge into a film, column, strip, plate, block, plug, pill, sheet, sponge or gel shape.

[0026] The present invention utilizes a salt (or complex) formed by acidic sodium hyaluronate, derived from two sodium hyaluronates of moderate molecular weight, and prototype ropivacaine as the primary sustained-release material and the primary sustained-release mechanism. The salt (or complex) formed by the two sodium hyaluronates of moderate molecular weight and prototype ropivacaine can release ropivacaine at two moderately different rates, providing sustained-release effects at both moderate and low rates, thereby achieving prolonged analgesia.

[0027] In the present invention, the salt (or complex) formed by acidic sodium hyaluronate converted from sodium hyaluronate of lower or higher molecular weight and the prototype ropivacaine releases ropivacaine too slowly (no or weak analgesic effect) or too quickly (short analgesic time or significant side effects), failing to meet the requirements of the present invention.

[0028] The present invention acidifies part of the sodium carboxyl groups in sodium hyaluronate, retains a portion of the sodium carboxyl groups, and does not completely acidify the sodium hyaluronate, which is beneficial to maintaining its relatively high hydrophilicity and preventing the aggregation and precipitation of the acid hyaluronate and the salt (or complex) formed with the prototype ropivacaine, thereby not affecting the sustained-release effect, and will not result in no or weak analgesic effect or short analgesic time, which would not meet the requirements of the present invention.

[0029] The invention is simultaneously formulated with an appropriate amount of ropivacaine hydrochloride to release ropivacaine at a conventional speed, thereby achieving faster analgesia.

[0030] The present invention also utilizes medium-viscosity hydroxypropyl cellulose, low-medium molecular weight sodium / calcium hyaluronate, higher molecular weight cross-linked sodium / calcium hyaluronate and cross-linked collagen as auxiliary sustained-release materials to enhance the sustained-release effect and prolong the sustained-release time, thereby further prolonging the analgesic time.

[0031] Calcifying low- to medium-molecular-weight sodium hyaluronate and higher-molecular-weight cross-linked sodium hyaluronate into low- to medium-molecular-weight sodium / calcium hyaluronate and higher-molecular-weight cross-linked sodium / calcium hyaluronate increases viscosity and enhances sustained-release. This allows the sodium ions in the sodium hyaluronate to be partially replaced by calcium ions, which helps maintain its relatively high hydrophilicity and prevents aggregation or precipitation, which could lead to unpredictable drug release.

[0032] The functions of medium-viscosity hydroxypropyl cellulose also include: 1) preventing the aggregation and precipitation of acid sodium hyaluronate and its salt (or complex) formed with prototype ropivacaine, especially in the presence of salt, especially in high ionic strength conditions;

[0033] 2) It can also prevent the aggregation and precipitation of high molecular weight cross-linked sodium hyaluronate in the presence of salt, especially in high ionic strength conditions, especially in the presence of calcium salts and magnesium salts.

[0034] In the present invention, hydroxypropyl cellulose with a lower viscosity has a poor blocking effect due to its low viscosity, making it difficult to prevent aggregation and precipitation, and thus failing to achieve the aforementioned effects. Hydroxypropyl cellulose with a higher viscosity, however, has a high viscosity, making it difficult to increase the dosage, resulting in poor salt resistance, and also failing to prevent aggregation and precipitation, and thus failing to achieve the aforementioned effects. Furthermore, its high viscosity makes handling difficult or the process complicated, for example, the aforementioned room temperature storage time (i.e., the time the salt (or complex) formed between sodium acid hyaluronate and prototype ropivacaine) is too long.

[0035] Medium-viscosity hydroxypropyl cellulose cannot achieve the above-mentioned effects, which will affect the sustained-release effect, resulting in no or weak analgesic effect or short analgesic time, making it difficult to achieve long-term analgesia, and even causing "dumping" of ropivacaine hydrochloride, that is, a one-time rapid release, which may have serious consequences.

[0036] The advantages of this invention over the prior art are:

[0037] 1) It can relieve pain quickly and for a longer period of time, and the pain relief time is consistent with clinical needs, neither too long nor too short;

[0038] 2) Lower incidence of adverse reactions;

[0039] 3) Good stability, salt resistance and high ionic strength resistance;

[0040] 4) Don’t “pour out”.

[0041] Example

[0042] The following non-selective examples, i.e., methods for preparing implants, further describe preferred embodiments within the scope of the present invention. Many variations of these embodiments are possible within the scope of the present invention.

[0043] Example 1

[0044] 1) Sodium hyaluronate with a molecular weight of 2000 to 10,000 (Daltons), sodium hyaluronate with a molecular weight of 50,000 to 100,000 (Daltons), and medium viscosity hydroxypropyl cellulose Klucel JF is dispersed in water, wherein the concentration of sodium hyaluronate with a molecular weight of 2,000 to 10,000 daltons is 23% wt / wt (based on 100% of the final total amount, i.e., 23 parts per 100 parts by weight), the concentration of sodium hyaluronate with a molecular weight of 50,000 to 100,000 daltons is 13% wt / wt (based on 100% of the final total amount, i.e., 13 parts per 100 parts by weight), and the concentration of hydroxypropyl cellulose is 4% wt / wt (based on 100% of the final total amount, i.e., 4 parts per 100 parts by weight). Hydrochloric acid solution is added to convert the sodium hyaluronate into acid sodium hyaluronate, wherein the molar amount of hydrochloric acid is 0.7 times the molar amount of the total sodium in the sodium hyaluronate. The mixture is mixed to obtain a colloidal solution A.

[0045] 2) adding a dispersion of prototype ropivacaine nanopowder or its water to colloidal solution A, wherein the molar amount of ropivacaine is 0.98-1 times of the molar amount of the above-mentioned hydrochloric acid, and adding ropivacaine hydrochloride, wherein the molar amount of ropivacaine hydrochloride is 0.55 times of the molar amount of the above-mentioned hydrochloric acid, mixing, and standing at room temperature for 12 hours to obtain colloidal solution B;

[0046] 3) Adding cross-linked sodium hyaluronate with a molecular weight of 800,000-1.2 million Daltons to colloidal solution B at a concentration of 3% wt / wt (based on the final total amount of 100%, i.e., 3 parts per 100 parts by weight) to obtain colloidal solution C;

[0047] 4) Add calcium chloride solution to colloidal solution C and mix thoroughly until 16% (in moles) of the total sodium ions in the three sodium hyaluronates are replaced by calcium ions. Mix thoroughly and allow to stand at room temperature for 2 days to form colloidal solution D.

[0048] 5) adding an aqueous solution of collagen and an aqueous solution of glutamyl endopeptidase to the colloidal solution D, respectively, wherein the concentration of the collagen is 5% wt / wt (based on the final total amount of 100%, i.e., 5 parts per 100 parts by weight), the ratio of the amount of the glutamyl endopeptidase to the collagen is 7 U / g, and after mixing evenly, the temperature is maintained at 0°C to 4°C for 72 hours to allow the collagen to be substantially cross-linked, thereby obtaining a colloidal solution E;

[0049] 6) The colloidal solution E was placed in a container so that the liquid layer thickness was 1.6 mm, and freeze-dried to remove the solvent.

[0050] Comparative Example 1-1

[0051] The sodium hyaluronate with a molecular weight of 2000 to 10,000 (Daltons) in Example 1 was replaced with sodium hyaluronate with a molecular weight of 200 to 500 (Daltons), and the other conditions remained unchanged.

[0052] Comparative Example 1-2

[0053] The sodium hyaluronate 5 with a molecular weight of 50,000 to 100,000 (Daltons) in Example 1 was replaced with sodium hyaluronate with a molecular weight of 200,000 to 500,000 (Daltons), and the other ingredients remained unchanged.

[0054] Example 2

[0055] 1) Sodium hyaluronate with a molecular weight of 2000 to 10,000 (Daltons), sodium hyaluronate with a molecular weight of 50,000 to 100,000 (Daltons), and medium viscosity hydroxypropyl cellulose Klucel JF is dispersed in water, wherein the concentration of sodium hyaluronate with a molecular weight of 2,000 to 10,000 daltons is 26% wt / wt (based on the final total amount of 100%, i.e., 26 parts per 100 parts by weight), the concentration of sodium hyaluronate with a molecular weight of 50,000 to 100,000 daltons is 12% wt / wt (based on the final total amount of 100%, i.e., 12 parts per 100 parts by weight), and the concentration of hydroxypropyl cellulose is 2% wt / wt (based on the final total amount of 100%, i.e., 2 parts per 100 parts by weight). Hydrochloric acid solution is added to convert the sodium hyaluronate into acid sodium hyaluronate, wherein the molar amount of hydrochloric acid is 0.8 times the molar amount of the total sodium in the sodium hyaluronate. The mixture is mixed to obtain a colloidal solution A.

[0056] 2) adding a dispersion of prototype ropivacaine nanopowder or its water to colloidal solution A, wherein the molar amount of ropivacaine is 0.98-1 times of the molar amount of the above-mentioned hydrochloric acid, and adding ropivacaine hydrochloride, wherein the molar amount of ropivacaine hydrochloride is 0.6 times of the molar amount of the above-mentioned hydrochloric acid, mixing, and standing at room temperature for 12 hours to obtain colloidal solution B;

[0057] 3) Adding cross-linked sodium hyaluronate with a molecular weight of 800,000-1.2 million Daltons to colloidal solution B at a concentration of 4% wt / wt (based on the final total amount of 100%, i.e., 4 parts per 100 parts by weight) to obtain colloidal solution C;

[0058] 4) Add calcium chloride solution to colloidal solution C and mix thoroughly until 12% (in moles) of the total sodium ions in the three sodium hyaluronates are replaced by calcium ions. Mix thoroughly and allow to stand at room temperature for 2 days to form colloidal solution D.

[0059] 5) Adding an aqueous solution of collagen and an aqueous solution of glutamyl endopeptidase to the colloidal solution D, respectively, wherein the concentration of the collagen is 8% wt / wt (based on the final total amount of 100%, i.e., 8 parts per 100 parts by weight), the ratio of the amount of the glutamyl endopeptidase to the collagen is 5 U / g, and after mixing evenly, maintaining the temperature at 0°C to 4°C for 72 hours to allow the collagen to be substantially cross-linked, thereby obtaining a colloidal solution E;

[0060] 6) The colloidal solution E was placed in a container so that the liquid layer thickness was 1.5 mm, and freeze-dried to remove the solvent.

[0061] Comparative Example 2-1

[0062] 90% of the amount of sodium hyaluronate with a molecular weight of 2000 to 10,000 (Daltons) in Example 2 (i.e., 10% of the original amount) was replaced with sodium hyaluronate with a molecular weight of 50,000 to 100,000 (Daltons), and the rest remained unchanged.

[0063] Comparative Example 2-2

[0064] 90% of the amount of sodium hyaluronate with a molecular weight of 50,000 to 100,000 (Daltons) in Example 2 (i.e., 10% of the original amount) was replaced with sodium hyaluronate with a molecular weight of 2,000 to 10,000 (Daltons), and the rest remained unchanged.

[0065] Example 3

[0066] 1) Sodium hyaluronate with a molecular weight of 2000 to 10,000 (Daltons), sodium hyaluronate with a molecular weight of 50,000 to 100,000 (Daltons), and medium viscosity hydroxypropyl cellulose Klucel JF is dispersed in water, wherein the concentration of sodium hyaluronate with a molecular weight of 2,000 to 10,000 daltons is 22% wt / wt (based on 100% of the final total amount, i.e., 22 parts per 100 parts by weight), the concentration of sodium hyaluronate with a molecular weight of 50,000 to 100,000 daltons is 14% wt / wt (based on 100% of the final total amount, i.e., 14 parts per 100 parts by weight), and the concentration of hydroxypropyl cellulose is 3% wt / wt (based on 100% of the final total amount, i.e., 3 parts per 100 parts by weight). Hydrochloric acid solution is added to convert the sodium hyaluronate into acid sodium hyaluronate, wherein the molar amount of hydrochloric acid is 0.8 times the molar amount of the total sodium in the sodium hyaluronate. The mixture is mixed to obtain a colloidal solution A.

[0067] 2) adding a dispersion of prototype ropivacaine nanopowder or its water to colloidal solution A, wherein the molar amount of ropivacaine is 0.98-1 times of the molar amount of the above-mentioned hydrochloric acid, and adding ropivacaine hydrochloride, wherein the molar amount of ropivacaine hydrochloride is 0.6 times of the molar amount of the above-mentioned hydrochloric acid, mixing, and standing at room temperature for 12 hours to obtain colloidal solution B;

[0068] 3) Adding cross-linked sodium hyaluronate with a molecular weight of 800,000-1.2 million Daltons to colloidal solution B at a concentration of 2% wt / wt (based on the final total amount of 100%, i.e., 2 parts per 100 parts by weight) to obtain colloidal solution C;

[0069] 4) Add calcium chloride solution to colloidal solution C and mix thoroughly until 16% (in moles) of the total sodium ions in the three sodium hyaluronates are replaced by calcium ions. Mix thoroughly and allow to stand at room temperature for 2 days to form colloidal solution D.

[0070] 5) Adding an aqueous solution of collagen and an aqueous solution of glutamyl endopeptidase to the colloidal solution D, respectively, wherein the concentration of the collagen is 3% wt / wt (based on the final total amount of 100%, that is, 3 parts per 100 parts by weight), the ratio of the amount of the glutamyl endopeptidase to the collagen is 3 U / g, and after mixing evenly, maintaining the temperature at 0°C to 4°C for 48 hours to allow the collagen to be substantially cross-linked, thereby obtaining a colloidal solution E;

[0071] 6) The colloidal solution E was placed in a container so that the liquid layer thickness was 1.5 mm, and freeze-dried to remove the solvent.

[0072] Comparative Example 3-1

[0073] The concentration of hydroxypropyl cellulose in Example 3 was changed from 3% wt / wt to 0.3% wt / wt, and the other contents remained unchanged.

[0074] Comparative Example 3-2

[0075] The concentration of hydroxypropyl cellulose in Example 3 was changed from 3% wt / wt to 8% wt / wt, and the other contents remained unchanged.

[0076] Example 4

[0077] 1) Sodium hyaluronate with a molecular weight of 2000 to 10,000 (Daltons), sodium hyaluronate with a molecular weight of 50,000 to 100,000 (Daltons), and medium viscosity hydroxypropyl cellulose Klucel JF is dispersed in water, wherein the concentration of sodium hyaluronate with a molecular weight of 2,000 to 10,000 daltons is 21% wt / wt (based on the final total amount of 100%, i.e., 21 parts per 100 parts by weight), the concentration of sodium hyaluronate with a molecular weight of 50,000 to 100,000 daltons is 15% wt / wt (based on the final total amount of 100%, i.e., 15 parts per 100 parts by weight), and the concentration of hydroxypropyl cellulose is 3% wt / wt (based on the final total amount of 100%, i.e., 3 parts per 100 parts by weight). Hydrochloric acid solution is added to convert the sodium hyaluronate into acid sodium hyaluronate, wherein the molar amount of hydrochloric acid is 0.7 times the molar amount of the total sodium in the sodium hyaluronate. The mixture is mixed to obtain a colloidal solution A.

[0078] 2) adding a dispersion of prototype ropivacaine nanopowder or its water to colloidal solution A, wherein the molar amount of ropivacaine is 0.98-1 times of the molar amount of the above-mentioned hydrochloric acid, and adding ropivacaine hydrochloride, wherein the molar amount of ropivacaine hydrochloride is 0.4 times of the molar amount of the above-mentioned hydrochloric acid, mixing, and standing at room temperature for 12 hours to obtain colloidal solution B;

[0079] 3) Adding cross-linked sodium hyaluronate with a molecular weight of 800,000-1.2 million Daltons to colloidal solution B at a concentration of 4% wt / wt (based on the final total amount of 100%, i.e., 4 parts per 100 parts by weight) to obtain colloidal solution C;

[0080] 4) Add calcium chloride solution to colloidal solution C and mix until 10% (in moles) of the total sodium ions in the three sodium hyaluronates are replaced by calcium ions. Mix thoroughly and let stand at room temperature for 2 days to form colloidal solution D.

[0081] 5) Adding an aqueous solution of collagen and an aqueous solution of glutamyl endopeptidase to colloidal solution D, respectively, wherein the concentration of the collagen is 2% wt / wt (based on the final total amount of 100%, i.e., 2 parts per 100 parts by weight), the ratio of the amount of the glutamyl endopeptidase to the collagen is 1 U / g, and after mixing evenly, maintaining the temperature at 0°C to 4°C for 72 hours to allow the collagen to be substantially cross-linked, thereby obtaining colloidal solution E;

[0082] 6) The colloidal solution E was placed in a container so that the liquid layer thickness was 2 mm, and freeze-dried to remove the solvent.

[0083] Comparative Example 4-1

[0084] The concentration of the cross-linked sodium hyaluronate with a molecular weight of 800,000-1.2 million Daltons in Example 4 was changed from 4% wt / wt to 0.5% wt / wt, while other parameters remained unchanged.

[0085] Comparative Example 4-2

[0086] The concentration of cross-linked sodium hyaluronate with a molecular weight of 800,000-1.2 million Daltons in Example 4 was changed from 4% wt / wt to 8% wt / wt, while other parameters remained unchanged.

[0087] Example 5

[0088] 1) Sodium hyaluronate with a molecular weight of 2000 to 10,000 (Daltons), sodium hyaluronate with a molecular weight of 50,000 to 100,000 (Daltons), and medium viscosity hydroxypropyl cellulose Klucel JF is dispersed in water, wherein the concentration of sodium hyaluronate with a molecular weight of 2,000 to 10,000 daltons is 27% wt / wt (based on the final total amount of 100%, i.e., 27 parts per 100 parts by weight), the concentration of sodium hyaluronate with a molecular weight of 50,000 to 100,000 daltons is 12% wt / wt (based on the final total amount of 100%, i.e., 12 parts per 100 parts by weight), and the concentration of hydroxypropyl cellulose is 2% wt / wt (based on the final total amount of 100%, i.e., 2 parts per 100 parts by weight). Hydrochloric acid solution is added to convert the sodium hyaluronate into acid sodium hyaluronate, wherein the molar amount of hydrochloric acid is 0.75 times the molar amount of the total sodium in the sodium hyaluronate. The mixture is mixed to obtain a colloidal solution A.

[0089] 2) adding a dispersion of prototype ropivacaine nanopowder or its water to colloidal solution A, wherein the molar amount of ropivacaine is 0.98-1 times of the molar amount of the above-mentioned hydrochloric acid, and adding ropivacaine hydrochloride, wherein the molar amount of ropivacaine hydrochloride is 0.5 times of the molar amount of the above-mentioned hydrochloric acid, mixing, and standing at room temperature for 12 hours to obtain colloidal solution B;

[0090] 3) Adding cross-linked sodium hyaluronate with a molecular weight of 800,000-1.2 million Daltons to colloidal solution B at a concentration of 3% wt / wt (based on the final total amount of 100%, i.e., 3 parts per 100 parts by weight) to obtain colloidal solution C;

[0091] 4) Add calcium chloride solution to colloidal solution C and mix thoroughly until 18% (in moles) of the total sodium ions in the three sodium hyaluronates are replaced by calcium ions. Mix thoroughly and allow to stand at room temperature for 2 days to form colloidal solution D.

[0092] 5) adding an aqueous solution of collagen and an aqueous solution of glutamyl endopeptidase to the colloidal solution D, respectively, wherein the concentration of the collagen is 5% wt / wt (based on the final total amount of 100%, i.e., 5 parts per 100 parts by weight), the ratio of the amount of the glutamyl endopeptidase to the collagen is 7 U / g, and after mixing evenly, the temperature is maintained at 0°C to 4°C for 72 hours to allow the collagen to be substantially cross-linked, thereby obtaining a colloidal solution E;

[0093] 6) The colloidal solution E was placed in a container so that the liquid layer thickness was 1.8 mm, and freeze-dried to remove the solvent.

[0094] Comparative Example 5-1

[0095] In Example 5, 16% (in moles) of the total sodium ions in the three sodium hyaluronates was replaced by calcium ions to 1%, while the other contents remained unchanged.

[0096] Comparative Example 5-2

[0097] The method described in step 5) of Example 5 was modified as follows, and the other methods remained unchanged:

[0098] Separately, an aqueous solution of collagen and an aqueous solution of glutamyl endopeptidase having the same volume as that in Example 5 were taken, wherein the amount of the collagen and the glutamyl endopeptidase was the same as that in Example 5, mixed well, and maintained at 0°C to 4°C for 72 hours to allow the collagen to be substantially cross-linked. The mixture was then added to colloidal solution D and mixed well to obtain colloidal solution E.

[0099] Example 6

[0100] 1) Sodium hyaluronate with a molecular weight of 2000 to 10,000 (Daltons), sodium hyaluronate with a molecular weight of 50,000 to 100,000 (Daltons), and medium viscosity hydroxypropyl cellulose Klucel JF is dispersed in water, wherein the concentration of sodium hyaluronate with a molecular weight of 2,000 to 10,000 daltons is 26% wt / wt (based on 100% of the final total amount, i.e., 23 parts per 100 parts by weight), the concentration of sodium hyaluronate with a molecular weight of 50,000 to 100,000 daltons is 11% wt / wt (based on 100% of the final total amount, i.e., 13 parts per 100 parts by weight), and the concentration of hydroxypropyl cellulose is 3% wt / wt (based on 100% of the final total amount, i.e., 4 parts per 100 parts by weight). Hydrochloric acid solution is added to convert the sodium hyaluronate into acid sodium hyaluronate, wherein the molar amount of hydrochloric acid is 0.65 times the molar amount of the total sodium in the sodium hyaluronate. The mixture is mixed to obtain a colloidal solution A.

[0101] 2) adding a dispersion of prototype ropivacaine nanopowder or its water to colloidal solution A, wherein the molar amount of ropivacaine is 0.98-1 times of the molar amount of the above-mentioned hydrochloric acid, and adding ropivacaine hydrochloride, wherein the molar amount of ropivacaine hydrochloride is 0.55 times of the molar amount of the above-mentioned hydrochloric acid, mixing, and standing at room temperature for 12 hours to obtain colloidal solution B;

[0102] 3) Adding cross-linked sodium hyaluronate with a molecular weight of 800,000-1.2 million Daltons to colloidal solution B at a concentration of 3% wt / wt (based on the final total amount of 100%, i.e., 3 parts per 100 parts by weight) to obtain colloidal solution C;

[0103] 4) Add calcium chloride solution to colloidal solution C and mix thoroughly until 12% (in moles) of the total sodium ions in the three sodium hyaluronates are replaced by calcium ions. Mix thoroughly and allow to stand at room temperature for 2 days to form colloidal solution D.

[0104] 5) adding an aqueous solution of collagen and an aqueous solution of glutamyl endopeptidase to the colloidal solution D, respectively, wherein the concentration of the collagen is 5% wt / wt (based on the final total amount of 100%, i.e., 5 parts per 100 parts by weight), the ratio of the amount of the glutamyl endopeptidase to the collagen is 8 U / g, and the temperature is maintained at 0°C to 4°C for 72 hours to allow the collagen to be substantially cross-linked, thereby obtaining a colloidal solution E;

[0105] 6) The colloidal solution E was placed in a container so that the liquid layer thickness was 2 mm, and freeze-dried to remove the solvent.

[0106] Comparative Example 6-1

[0107] The molar amount of hydrochloric acid in Example 6 was changed from 0.65 times the molar amount of the total sodium in the above sodium hyaluronate to 0.05 times the molar amount of the total sodium in the above sodium hyaluronate, and the other conditions remained unchanged.

[0108] Comparative Example 6-2

[0109] The molar amount of hydrochloric acid in Example 6 was changed from 0.65 times the molar amount of the total sodium in the above sodium hyaluronate to 0.98 times the molar amount of the total sodium in the above sodium hyaluronate, and the other conditions remained unchanged.

[0110] The method of the above sodium hyaluronate is as follows:

[0111] Dissolve the commercially available sodium hyaluronate with a molecular weight of 500,000-1,000,000 Daltons in a three-necked flask, and add a solution of hydrogen peroxide and ascorbic acid with a molar ratio of 3:1 at a uniform rate while stirring until the concentration of hydrogen peroxide is 2-4%. Adjust the pH to 4, heat in a water bath to 45-55°C, and keep the reaction for 10-30 minutes. Then add a 5% sodium hydroxide solution to the reaction solution, adjust the pH to 7-7.5, and use a pore size of 500,000 Daltons, 200,000 Daltons, and 100,000 Daltons in sequence. , 50,000 Daltons, 10,000 Daltons, 2,000 Daltons, 500 Daltons, and 200 Daltons nanofiltration membranes were used to filter the mixture, and solutions of sodium hyaluronate with molecular weights of 200,000 Daltons-500,000 Daltons, 50,000 Daltons-100,000 Daltons, 2,000 Daltons-10,000 Daltons, and 200 Daltons-500 Daltons were intercepted; acetone with a volume 2-3 times that of the reactant was added dropwise under stirring, and the mixture was allowed to stand overnight. The degradation products were filtered out, washed with acetone, and dried under reduced pressure.

[0112] Test Case

[0113] The samples of the embodiment and the comparative example were cut into 2CM×1.5CM implant sponges and sterilized by γ-ray irradiation.

[0114] Animal in vivo toxicity tests, cytotoxicity tests, pyrogen tests, hemolysis tests, and intradermal injection experiments have shown that the implantable sponge is non-toxic, has no hemolytic effect, is non-irritating, does not contain pyrogenic substances, has stable performance, and has good biocompatibility.

[0115] The above-mentioned sponge is implanted at the same time after apical cyst removal to treat apical cyst

[0116] 882 patients with periapical cysts were randomly divided into one experimental group and two control groups, each with 294 patients. After apical cyst removal, each group received the sponge samples from the examples and control examples described above. Following implantation, the mucoperiosteum was repaired, the wound was sutured conventionally, and a pressure bandage was applied. Antibiotics were administered postoperatively to prevent infection, and the sutures were removed 7 days later.

[0117] The analgesic effects of the sponge samples containing the embodiment and the control were compared. The visual analogue scale (VAS) of pain was calculated for the patients in the embodiment and control groups at 6, 12, 24, 36, 48, and 72 hours after surgery, both at rest and in motion. The score for no pain was 0, for disturbing sleep was 5, and for severe pain was 10. The higher the score, the more severe the pain.

[0118] The incidence of adverse reactions to postoperative analgesia in patients in the embodiment and control groups was statistically analyzed, including symptoms such as nausea, dizziness, palpitations, and sweating. The adverse reaction (incidence) rate = number of adverse reaction cases / total number of cases × 100%.

[0119] The VAS score results of the subjects after receiving the sample treatment are shown in Table 1.

[0120] The adverse reaction (incidence) rates of the subjects after receiving the sample treatment are shown in Table 2.

[0121] Table 1-1 VAS score results of subjects after receiving sample treatment

[0122] 6 hours after surgery 12 hours after surgery 24 hours after surgery 36 hours after surgery 48 hours after surgery 72 hours after surgery Example 1 1.33±0.32 1.84±0.33 2.25±0.34 2.48±0.36 2.67±0.40 3.06±0.45 Comparative Example 1-1 1.48±0.33 2.78±0.34 3.27±0.41 3.73±0.46 4.18±0.52 4.67±0.55 Comparative Example 1-2 1.07±0.25 1.56±0.27 2.42±0.46 3.57±0.53 4.77±0.65 5.23±0.71

[0123] Table 1-2 VAS score results of subjects after receiving sample treatment

[0124] 6 hours after surgery 12 hours after surgery 24 hours after surgery 36 hours after surgery 48 hours after surgery 72 hours after surgery Example 2 1.53±0.31 2.05±0.32 2.32±0.35 2.55±0.37 2.78±0.47 3.27±0.46 Comparative Example 2-1 1.18±0.32 1.72±0.35 2.27±0.38 3.15±0.48 4.08±0.54 5.69±0.58 Comparative Example 2-2 1.95±0.36 2.49±0.37 3.16±0.41 3.62±0.46 4.02±0.57 4.53±0.55

[0125] Table 1-3 VAS score results of subjects after receiving sample treatment

[0126] 6 hours after surgery 12 hours after surgery 24 hours after surgery 36 hours after surgery 48 hours after surgery 72 hours after surgery Example 3 1.24±0.27 1.57±0.32 2.04±0.33 2.48±0.35 2.83±0.37 3.07±0.38 Comparative Example 3-1 1.06±0.25 1.45±0.30 2.45±0.38 3.27±0.46 4.26±0.53 5.67±0.68 Comparative Example 3-2 -★ - - - - -

[0127] Note: Qualified samples were not obtained, and turbidity was not tested. Control Example 3-2 had a jelly-like consistency due to its high viscosity, making freeze-drying and other operations difficult. The prototype lidocaine was dispersed in a granular state, resulting in a turbid sample. However, the example sample was a clear (colloidal) solution before freeze-drying.

[0128] Table 1-4 VAS score results of subjects after receiving sample treatment

[0129] 6 hours after surgery 12 hours after surgery 24 hours after surgery 36 hours after surgery 48 hours after surgery 72 hours after surgery Example 4 1.22±0.23 1.51±0.34 2.25±0.37 2.67±0.38 2.97±0.39 3.42±0.46 Comparative Example 4-1 1.08±0.25 1.62±0.31 2.57±0.35 3.42±0.43 4.32±0.56 5.84±0.62 Comparative Example 4-2 -★ - - - - -

[0130] ★Note: No qualified samples were obtained and the turbidity was not tested. The control example 4-2 had a jelly-like sample due to its high viscosity, making freeze-drying and other operations more difficult.

[0131] Table 1-5 VAS score results of subjects after receiving sample treatment

[0132] 6 hours after surgery 12 hours after surgery 24 hours after surgery 36 hours after surgery 48 hours after surgery 72 hours after surgery Example 5 1.41±0.28 1.91±0.30 2.36±0.31 2.58±0.33 2.87±0.35 3.05±0.44 Comparative Example 5-1 1.15±0.23 1.78±0.27 2.63±0.29 3.35±0.37 3.95±0.52 4.83±0.58 Comparative Example 5-2 1.22±0.26 1.89±0.28 2.76±0.30 3.55±0.41 4.14±0.55 5.02±0.62

[0133] Table 1-6 VAS score results of subjects after receiving sample treatment

[0134] 6 hours after surgery 12 hours after surgery 24 hours after surgery 36 hours after surgery 48 hours after surgery 72 hours after surgery Example 6 1.34±0.25 1.82±0.28 2.21±0.30 2.47±0.32 2.75±0.36 3.02±0.43 Comparative Example 6-1 1.22±0.22 1.67±0.25 2.56±0.28 3.26±0.39 4.08±0.56 5.02±0.63 Comparative Example 6-2 1.82±0.26 2.27±0.30 2.87±0.34 3.58±0.45 4.04±0.52 4.42±0.55

[0135] Table 2-1 Adverse reaction rate results after subjects received sample treatment

[0136]

[0137]

[0138] Table 2-2 Adverse reaction rate results after subjects received sample treatment

[0139] Adverse reaction rate% Example 2 11 Comparative Example 2-1 27 Comparative Example 2-2 8

[0140] Table 2-3 Adverse reaction rate results after subjects received sample treatment

[0141] Adverse reaction rate% Example 3 16 Comparative Example 3-1 31 Comparative Example 3-2 -

[0142] Table 2-4 Adverse reaction rate results after subjects received sample treatment

[0143] Adverse reaction rate% Example 4 19 Comparative Example 4-1 37 Comparative Example 4-2 -

[0144] Table 2-5 Adverse reaction rate results after subjects received sample treatment

[0145]

[0146]

[0147] Table 2-6 Adverse reaction rate results after subjects received sample treatment

[0148] Adverse reaction rate% Example 6 12 Comparative Example 6-1 25 Comparative Example 6-2 10

[0149] The results showed that the embodiments had faster onset of action, better drug release performance, and better analgesic effect than the control examples, or had equivalent analgesic effect but lower incidence of adverse reactions.

[0150] The pain relief in the examples lasted for several days, with some improvement, then became consistent or worse, neither too long nor too short. Conventional gel sustained-release preparations only last a few to a dozen hours, while drugs dispersed in polyester-based sustained-release preparations like PCL can last for weeks to months—a significant difference between too long and too short for pain relief.

[0151] Some control examples had slightly better analgesic effects than the examples at the beginning, but the effects became worse in the later stages, and the incidence of side effects was relatively higher, which may be related to the faster drug release rate.

[0152] The initial analgesic effect of some control examples was poorer than that of the embodiment, and the incidence of side effects was slightly lower, which may be related to the lower drug release rate.

Claims

1. A method for preparing an implant sponge with low incidence of side effects, high safety, rapid and long-term analgesia, the method comprising: 1) Disperse sodium hyaluronate with a molecular weight of 2000 to 10,000 Daltons, sodium hyaluronate with a molecular weight of 50,000 to 100,000 Daltons, and medium-viscosity hydroxypropyl cellulose with a molecular weight of 100,000 to 200,000 Daltons in water, wherein the concentration of sodium hyaluronate with a molecular weight of 2000 to 10,000 Daltons is 20-30% wt / wt, i.e., it contains 20-30 parts per 100 parts by weight, the concentration of sodium hyaluronate with a molecular weight of 50,000 to 100,000 Daltons is 10-15% wt / wt, i.e., it contains 10-15 parts per 100 parts by weight, and the concentration of hydroxypropyl cellulose is 2-6% wt / wt, i.e., it contains 2-6 parts per 100 parts by weight, add hydrochloric acid solution to convert sodium hyaluronate into acid sodium hyaluronate, wherein the molar amount of hydrochloric acid is 0.7-0.8 times the molar amount of total sodium in the above sodium hyaluronate, mix well, and obtain colloidal solution A; 2) Adding the prototype ropivacaine nanometer powder or its aqueous dispersion to the colloidal solution A, wherein the molar amount of ropivacaine is 0.95-1 times the molar amount of the hydrochloric acid in the above-mentioned hydrochloric acid solution; and adding ropivacaine hydrochloride, wherein the molar amount of ropivacaine is 0.4-0.8 times the molar amount of the hydrochloric acid in the above-mentioned hydrochloric acid solution, mixing, and leaving at room temperature for 8-24 hours to obtain a colloidal solution B; 3) Adding cross-linked sodium hyaluronate with a molecular weight of 800,000-1.2 million Daltons to colloidal solution B at a concentration of 1-5% wt / wt, i.e., 1-5 parts per 100 parts by weight, to obtain colloidal solution C; 4) Add calcium salt solution to colloidal solution C, mix well, so that 10% to 20% of the total molar amount of sodium ions in the above three sodium hyaluronates are replaced by calcium ions, mix well, and leave at room temperature for 1-3 days to form colloidal solution D; 5) Adding an aqueous solution of collagen and an aqueous solution of glutamyl endopeptidase to the colloidal solution D, respectively, wherein the concentration of the collagen is 1-8% wt / wt, i.e., 1-8 parts per 100 parts by weight, and the ratio of the amount of the glutamyl endopeptidase to the collagen is 1-15 U / g. After mixing evenly, the temperature is maintained at 0° C. to 4° C. for 24-72 hours to make the collagen basically cross-linked, thereby obtaining a colloidal solution E; 6) The colloidal solution E is placed in a container so that the liquid layer thickness is 1-2 mm, and freeze-dried to remove the solvent.

2. The preparation method according to claim 1, characterized in that The concentration of sodium hyaluronate with a molecular weight of 2000 to 10,000 Daltons is 23%-28% wt / wt.

3. The preparation method according to claim 1, characterized in that The concentration of sodium hyaluronate with a molecular weight of 50,000 to 100,000 Daltons is 12%-13% wt / wt.

4. The preparation method according to claim 1, characterized in that The concentration of the hydroxypropyl cellulose is 3-4% wt / wt.

5. The preparation method according to claim 1, characterized in that The calcium salt includes calcium chloride, calcium acetate, calcium nitrate, calcium hydroxide or a mixture thereof.

6. The preparation method according to claim 1, characterized in that The usage ratio of the sodium hyaluronate with a molecular weight of 2000 to 10,000 Daltons to the sodium hyaluronate with a molecular weight of 50,000 to 100,000 Daltons is 2:0.8-1.

7. The preparation method according to claim 1, characterized in that The usage ratio of the sodium hyaluronate with a molecular weight of 2000 to 10,000 Daltons to the sodium hyaluronate with a molecular weight of 50,000 to 100,000 Daltons is 2:

1.

8. The preparation method according to claim 1, characterized in that The thickness of the liquid layer is 1.3-1.8 mm.

9. The colloid aqueous solution according to claim 1, characterized in that The medium-viscosity hydroxypropyl cellulose has a molecular weight of 140,000 Daltons and a viscosity of 150-400 mPa·s at a concentration of 5% wt / wt.

10. The preparation method according to claim 1, characterized in that The preparation method also includes further preparing into a film, column, strip, plate, block, plug, pill, sheet, sponge or gel.